Predicting the risk and trigger thresholds for propagation of meteorological droughts to agricultural droughts in China based on Copula-Bayesian model - Cuiping Yang; Changhong Liu; Xuguang Xing; Xiaoyi Ma (Agricultural Water Management)
Meteorological droughts are propagated through atmospheric and hydrological cycles, ultimately triggering agricultural droughts. Accurate prediction of future meteorological to agricultural drought propagation is essential for developing early warning systems and managing agricultural water resources. However, the thresholds at which meteorological drought induce agricultural drought remains unclear. In this study, a drought propagation threshold framework based on a Copula-Bayesian model was developed to estimate the propagation time, probability, and triggering thresholds of meteorological drought to agricultural drought in China under future scenarios. The results indicated that meteorological and agricultural drought indices were projected to exhibit declining trends in the future, suggesting the intensification of drought severity across China. The drought propagation time was expected to shorten by 1.6–3 months in the future. Furthermore, the conditional probability for the propagation of meteorological droughts of varying severity to agricultural droughts was projected to increase by 10.9–26.4 %. Southern China (SC) and the Yangtze River Basin (YRB) regions emerged as high-risk regions for drought propagation, where average conditional probabilities were 57.2–65.1 % and 49.1–57.4 %, respectively. The drought propagation thresholds were projected to increase in the future, indicating heightened vulnerability of agricultural droughts to meteorological droughts. The triggering thresholds for drought in SC (−0.99 to −0.87) and YRB (−1.20 to −0.94) were relatively high, where even mild meteorological droughts would induce moderate agricultural droughts in the future. By contrast, the predicted trigger thresholds were relatively low for the Northeast China Plain (−1.92 to −1.65) and North China Plain (−1.69 to −1.50). Across China, temperature emerged as the primary driver of changes in trigger thresholds, with its relative contribution estimated to be 43.1–47.2 %. Climate warming was projected to increase the future trigger thresholds in China. The findings assist policymakers in formulating effective agricultural management strategies to address future agricultural drought risks.